In-situ-construction of BiOI/UiO-66 heterostructure via nanoplate-on-octahedron: A novel p-n heterojunction photocatalyst for efficient sulfadiazine elimination - Tianyu Wang; Chen Zhao; Linghui Meng; Li, Yujia; Hongyu Chu; Fei Wang; Yingru Tao; Liu, Wen; Chong-Chen Wang (Chemical Engineering Journal, 2023)
Sulfadiazine (SDZ), as a broad-spectrum pharmaceutical antibiotic, has drawn extensive attention owing to its wide application and persistence. Photocatalytic oxidation has been considered as a high-efficiency and environment-friendly technology for degrading organic contaminants. A novel BiOI/UiO-66 p-n heterojunction (BiU-x) was fabricated via the in-situ deposition of p-type BiOI nanoplates on n-type UiO-66 octahedrons with the aid of a controlled precipitation method. The optimizing BiU-9 heterojunction exhibited a remarkably enhanced photocatalytic efficiency in removing SDZ, in which the SDZ (5 mg/L) removal efficiency over BiU-9 (0.5 g/L) reached nearly 100 % within 90 min of visible light irradiation. The influence of some important environmental factors (e.g., photocatalyst dosage, pH, co-existing inorganic anions and real sunlight irradiation) were systematically investigated. Such improvement mechanism should be assigned to the following three factors. Firstly, the introduction of narrow gap semiconductor BiOI effectively improved photo adsorption capacity. Secondly, benefiting by the large specific surface area, the involvement of UiO-66 contributed to boost the surface active sites. Most importantly, an internal electric field at the contact interface between UiO-66 and BiOI accelerated the separation of photo-generated electrons and holes. Furthermore, ·O2− and photo-generated holes were identified as the dominating reactive species accounting for the SDZ removal. The decomposition pathways of SDZ and ecotoxicities of the intermediates were analyzed via combing with LC-MS/MS and T.E.S.T theoretical calculation. This work may provide an alternative way for enhanced photocatalytic performance of MOF-based materials through construction of p-n heterojunction with bismuth-based semiconductors.
Keywords: Antibiotic removal; BiOI; p-n heterojunction; Photocatalysis; UiO-66